(untitled) (Research, Society and Development, 2021)
Introduction: Premature, low weight and seriously ill babies need better support, more judicious and humanized care, for this reason, they are constantly admitted to Neonatal Intensive Care Units. Objective: The objective of the research will be to identify through scientific research the humanization process carried out by nurses in Neonatal Intensive Care Units and describe the importance of this practice. Methodology: This is a study with a qualitative approach, descriptive, of the integrative review type, which will address humanization in the Neonatal Intensive Care Units. It was performed by searching a database available in the Virtual Health Library (VHL) using the descriptors Neonatal intensive care unit; Nursing; Humanization. Results and discussions: Two categories were created: Category 1: The impact of the Intensive Care Unit on the newborn’s relatives; Category 2: The importance of the Kangaroo Method in the humanization process of the Neonatal Intensive Care Unit. Final Considerations: Through the study, it was possible to identify the great importance of humanized care in Neonatal Intensive Care Units, due to the evolution of the newborn’s clinical condition in its entirety, the participation of the family in this adverse environment shows beneficial effects for themselves and for all health professionals involved.